Internet of robotic things: Design and develop the quality of service framework for the healthcare sector using CoAP - Kumar, Arun; Sharma, Sharad (IAES International Journal of Robotics and Automation (IJRA), 2021)
The number of robotics used globally is gradually growing, according to a variety of research. They are becoming more and more popular in different workplaces, like manufacturing, distribution, medical conditions, military, inaccessible areas, etc. The int ernet of things (IoT) and robotics groups have until now been guided by a set of, but somewhat compatible, goals, which are mainly to help knowledge systems in the field of general sensing, tracking, and monitoring. Therefore, the development of an interne t of robotic things (IoRT), which incorporates the outcome from both cultures, is progressively said to have a significant added benefit. Internet of robotic thin gs, the intersection of the Internet of Things and robotics, is where self - sufficient machines will assemble information from various sensors and speak with one another to perform errands including basic reasoning. As the name suggests, IoRT is the combination of two front - line innovations, the internet of things and robotics . People can manage any electronic device in homes with IoT and can also be used in contactless applications in healthcare. The constrained application protocol (CoAP), for the management and control of a community of homogeneous sensor modules, has recently endorsed multicast c ommunications in IoRT. It will boost connectivity performance, less power consumption due to data aggregation, and enhanced security features with DTLS security features for various applications for the internet of things . This paper presents an implementa tion of the CoAP framework on IoRT sky motes using the C ontiki C ooja Simulator that will be a useful healthcare sector that will confirm their potential and therefore, new research directions are outlined.